HISTORY OF MEXICAN OIL - Cárdenas, Cuauhtémoc (Archipielago. Revista cultural de nuestra América, 2010)
At the recent inauguration of the "Exposition on the History of Oil in Mexico" in the Industries Club in Mexico City, the engineer Cuauhtémoc Cardenas gave a lecture published here, in which he reminds us of the difficulties that this country had to face, particularly his father, General Lázaro Cárdenas, in making the expropriation of oil possible on March 18, 1938. This was doubtless one of the most significant and transcendent acts in the history of Mexico, a topic which has recently received reawakened social, economic and political attention.